Scalable Information Systems : 5th International Conference, INFOSCALE 2014, Seoul, South Korea, September 25-26, 2014, Revised selected papers /: 5th International Conference, INFOSCALE 2014, Seoul, South Korea, September 25-26, 2014, Revised selected papers. (2015) - Unknown
No abstract available